2019
DOI: 10.1016/j.jid.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dermatitis in America Study: A Cross-Sectional Study Examining the Prevalence and Disease Burden of Atopic Dermatitis in the US Adult Population

Abstract: Population-based estimates on the prevalence of atopic dermatitis in adults vary widely. The objectives of this study were to determine the prevalence of atopic dermatitis in the population of the United States, the distribution of disease severity, and its impact on health-related quality of life. Among 1,278 participating adults, the prevalence (95% confidence interval) of atopic dermatitis was 7.3% (5.9e8.8). Overall, 60.1% (56.1e64.1) of participants were classified as having mild, 28.9% (25.3e32.7) as hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
172
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 316 publications
(184 citation statements)
references
References 32 publications
6
172
1
5
Order By: Relevance
“…We found that the prevalence of patients requiring repeat antidepressant prescriptions is twice as high for patients with AD using high amounts of TCS vs. those who use low amounts of TCS (12% vs. 6%, Table ). These data confirm previously reported associations between AD and depression in adults and children and further validate the use of quantitative drug prescribing data to obtain clinically relevant ‘holistic’ treatment readouts. In this regard, perhaps the most obvious application of the approach presented herein will be the confirmation and quantification of the benefit of novel and often resource‐intensive treatments (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…We found that the prevalence of patients requiring repeat antidepressant prescriptions is twice as high for patients with AD using high amounts of TCS vs. those who use low amounts of TCS (12% vs. 6%, Table ). These data confirm previously reported associations between AD and depression in adults and children and further validate the use of quantitative drug prescribing data to obtain clinically relevant ‘holistic’ treatment readouts. In this regard, perhaps the most obvious application of the approach presented herein will be the confirmation and quantification of the benefit of novel and often resource‐intensive treatments (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of adult AD varies widely from country to country, as it is 2.7-3.1% in Korea [3,4] and 7.3% in the United States [5]. AD has a significantly higher prevalence among females (9.3-10%) than males [5,6], and the Nurses' Health Study 2 (NHS2), which analyzed nurse health in the United States, reported that the prevalence of AD among female nurses was 10.1%, higher than that among all adults [7].…”
Section: Introductionmentioning
confidence: 99%
“…En México, a diferencia de otros, los médicos especialistas principalmente de alergia e inmunología clínica pueden atender tanto a población pediátrica como adultos, esto explica porque 62 % de los pacientes atendidos es mayor de 18 años, resultado que contrasta por lo publicado en la literatura, donde la prevalencia de DA es mayor en población pediátrica. 14,15,16 Existen diferentes criterios clínicos para el diagnóstico de DA; en México, el Consenso Mexicano para el Diagnóstico y Tratamiento de la Dermatitis Atópica en Niños y Adultos y las Guías CENETEC (Centro Nacional de Excelencia Tecnológica en Salud) recomiendan utilizar los criterios de Williams, por su sensibilidad y especifi cidad, además de su fácil aplicación (cuadro 1).…”
Section: Discussionunclassified